A comparative analysis of impulse buying strategies : case study of an online women apparel store - Malik, Anam (2019)
This paper presents a statistical analysis of different strategies that are used commonly by ecommerce companies to trigger impulse purchasing. The goal of the study is to offer insights to marketers and entrepreneurs as to which strategies perform successfully with internet users. The study attempts to measure the effectiveness of these strategies on four metrics, namely number of sales, average order value, number of repeat customers and average session duration. By deploying different strategies on an online women fashion store, data was collected from users from a defined set of demographics. This data was analyzed with the help of various analytics tools in order to put together actionable information for marketers and entrepreneurs.